Efficiency Enhancement Mechanism of an Underlying Layer in GaInN‐Based Green Light–Emitting Diodes. Issue 7 (17th December 2019) - Han, Dong-Pyo; Ishimoto, Seiji; Mano, Ryoya; Lu, Weifang; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu
Abstract : To investigate the mechanism of efficiency enhancement achieved by introducing underlying layers (ULs) in green light–emitting diodes (LEDs), this study compares green GaInN‐based LEDs with an identical epitaxial structure and chip structure comprising different types of ULs, i.e., without an UL or with a GaInN or AlInN UL. To this end, the samples are analyzed with respect to several characteristics, such as their electroluminescence spectra, internal quantum efficiency, recombination coefficients, joint density of states, localized state, and Stokes shift. Based on these analyses and considerations, a mechanism of efficiency enhancement achieved by introducing ULs is proposed, and the degradation mechanisms responsible for the green gap, efficiency droop, and electrical potential drop in green LEDs are also discussed. The results show that the piezoelectric field in the In‐clustering region and the nonradiative recombination center simultaneously play crucial roles in the degradation mechanisms for green LEDs. Abstract : This study compares green GaInN‐based light‐emitting diodes (LEDs) with identical structures composed of different types of underlying layers (ULs), that is, GaInN and AlInN ULs. The results show that the GaInN UL reduces not only nonradiative recombination centers but also the piezoelectric field in active region. However, the AlInN ULs exhibit only a weak effect on the piezoelectric field, causing the droop.